Gender, financial literacy and ethical sensitivity: a behavioural model of Sharia investment decision making - Rofiatus Saadah, Karimatur; Rahmawati, Yunaita (Journal International Economic Sharia, 2025)
Objective: This paper examines the effect of gender, financial literacy, ethical sensitivity, and risk perception on ethical investment behavior under a Sharia-compliant setting.Methods:  A quantitative explanatory design was used, with data collected from surveys and moderation analysis conducted on financial experience with predictor outcome relations.Results:  The results show that gender, financial literacy, ethical sensitivity, and risk perception have significant positive impacts on the EIB. Financial literacy enhances this influence, allowing investors to incorporate ethical considerations and cognitive knowledge in Shariah investment. The joint predictors give a synergistic effect whereby both attribute and experiential knowledge are each significant in their worked contributions to ethical investment behavior.Novelty: This paper is the first study that links behavioral finance and Islamic ethical paradigms to show that cognitive, moral, and experiential motivations jointly influence individual ethical investment decisions. The inclusion of financial experience as a moderator may also serve to shed new light on the workings of morally-informed financial decision-making.Research Implication: The results have practical implications for policy makers and financial institutions to establish gender sensitive experience based training schemes that will improve ethical investment culture. This study contributes to the literature by associating BF with Sharia ethics, and sheds light on experiential learning to promote investor moral awareness and decision quality.